PENGARUH STRATEGI RETENSI KARYAWAN TERHADAP TURNOVER KARYAWAN DENGAN LOYALITAS KARYAWAN SEBAGAI VARIABEL MEDIASI PADA PT. BUMANIK - Tammy Putra Ramdhany; Recky Recky; Andhika Mochamad Siddiq; Kartika Nuradina; Prinska Damara Sastri (Jurnal Daya Saing, 2026)
This study focuses on evaluating the impact of employee retention strategies on employee turnover, with employee loyalty serving as a mediating variable at PT Bumanik. The research employed a quantitative explanatory approach. The sample consisted of 120 active employees selected using a purposive sampling technique. Data were collected through a questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that employee retention strategies have a positive and significant effect on employee loyalty. Conversely, both employee loyalty and employee retention strategies have a negative and significant effect on employee turnover. The mediation analysis confirms that employee loyalty significantly mediates the relationship between employee retention strategies and employee turnover. Overall, the implementation of effective employee retention strategies has been proven to enhance employee loyalty while simultaneously reducing turnover at PT Bumanik.